2012
DOI: 10.1155/2012/403531
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Oocyte Denudation and Intracytoplasmic Sperm Injection

Abstract: Objectives. To analyze the impact of oocyte denudation and microinjection timings on intracytoplasmic sperm injection (ICSI) outcomes. Study Design. We included ICSI cycles with the following parameters: rank 1 or 2, female age <36 years, male factor infertility, long protocol using GnRH agonist and rFSH for ovarian stimulation, and use of freshly ejaculated sperm (n = 110). Several ICSI parameters were analyzed according to the time between oocyte retrieval and denudation (T 1) and the time between denudatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 26 publications
0
47
2
Order By: Relevance
“…Our present study discovered DN-ICSI time interval acted as an independent predictor for clinical outcomes in ICSI cycles. Indeed, most investigators have showed the relation between DN-ICSI interval and fertilization rate [6,11,14,15]. Nevertheless, there are limited studies available for the influence on the clinical outcomes associated with raised DN-ICSI interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our present study discovered DN-ICSI time interval acted as an independent predictor for clinical outcomes in ICSI cycles. Indeed, most investigators have showed the relation between DN-ICSI interval and fertilization rate [6,11,14,15]. Nevertheless, there are limited studies available for the influence on the clinical outcomes associated with raised DN-ICSI interval.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that the procedure might achieve a better outcome if ICSI was performed immediately after denudation. Besides, Catherme patrat et al [6] performed logistic regression analysis on 110 cycles and found that in terms of the fertilization rate, an optimal time to carry out DN was within 3 h following OPU and performing ICSI soon after DN was a good choice. However, other researches did not confirm the optimal time to perform ICSI following DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature oocytes are at the stage of the second meiotic division (M II), which is sensitive to physical and chemical influences in cryopreservation. The release of oocytes from surrounding cumulus cells and granulosa (denudation) improves the oocyte survival rate [24].…”
Section: Morphological and Functional Evaluation Of Cryopreserved Oocmentioning
confidence: 99%
“…After oocyte pick up, every oocyte surrounded by its own CC was cultured individually in 30 μl microdrops of culture media (ISM1, Origio) under mineral oil (Liquid Paraffin, Origio) for at least two hours [22]. Decoronization was carried out by placing each cumulus oocyte complex (COC) in separated drops of recombinant human hyaluronidase (ICSI cumulase, Origio) under oil.…”
Section: Isolation and Collection Of Cumulus Cellsmentioning
confidence: 99%